Medicinal Plants Against Dental Caries: Research and Application of Their Antibacterial Properties - Marcela Alejandra Gloria-Garza; Gustavo Raúl Reyna-Martínez; Zacarías Jiménez-Salas; Eduardo Campos-Góngora; Miroslava Kačániová; Diana Elena Aguirre-Cavazos; Minerva Bautista-Villarreal; Catalina Leos-Rivas; Joel Horacio Elizondo-Luevano (Plants)
Dental caries remains one of the most widespread global health concerns, significantly affecting both oral and overall health. Conventional treatments typically rely on chemical-based products which, although effective, are often associated with undesirable side effects such as tooth staining, altered taste, and the development of antimicrobial resistance. As a response, plant-based natural alternatives have gained attention as promising strategies for the prevention and management of dental caries. This review highlights the antibacterial properties of medicinal plants and their potential applications in dentistry, with a particular focus on their activity against a broad range of bacteria and microorganisms involved in oral diseases. Numerous plant extracts and bioactive compounds—including polyphenols, flavonoids, and essential oils—have demonstrated antimicrobial, anti-inflammatory, and antioxidant properties that contribute to maintaining oral health. Although in vitro and in vivo studies support their therapeutic potential, clinical trials assessing long-term efficacy and safety remain scarce. Future research should prioritize the standardization of extraction methods, dosage, and formulations to facilitate the integration of these natural alternatives into conventional dental care practices.